1991
DOI: 10.1128/aem.57.11.3390-3393.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mesophilic lactic acid bacteria by using polymerase chain reaction-amplified variable regions of 16S rRNA and specific DNA probes

Abstract: Specific DNA probes based on variable regions Vl and V3 of 16S rRNA of lactic acid bacteria were designed. These probes were used in hybridization experiments with variable regions amplified by using the polymerase chain reaction. In this way, a rapid and sensitive method was developed for the identification and classification of Lactococcus and Leuconostoc species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(107 citation statements)
references
References 20 publications
1
95
0
2
Order By: Relevance
“…The objective of this study was to investigate the value of primer-specific P C R for identification of clinical isolates of S. epidermidis. Primer-specific PCR allows the detection of small amounts of D N A extracted directly from bacterial colonies or from a standardized bacterial suspension [25]. Primer-specific PCR is much faster and more reliable for the identification of S. epidermidis than the commercially available API ID32 STAPH system, allowing the assay to be performed in about 3 h. Ribotyping analysis has been widely used for comparing strains from a large variety of species because of its stability and reproducibility [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this study was to investigate the value of primer-specific P C R for identification of clinical isolates of S. epidermidis. Primer-specific PCR allows the detection of small amounts of D N A extracted directly from bacterial colonies or from a standardized bacterial suspension [25]. Primer-specific PCR is much faster and more reliable for the identification of S. epidermidis than the commercially available API ID32 STAPH system, allowing the assay to be performed in about 3 h. Ribotyping analysis has been widely used for comparing strains from a large variety of species because of its stability and reproducibility [20].…”
Section: Discussionmentioning
confidence: 99%
“…The primer-specific P C R was performed using the primers p2 (5 '-AAGGAGGTGATCCAGCCGCA-3') and pSe (5'-ACTCTATCTCTAGAGGGGTCAG-3') as described earlier [24]. PCR products were obtained by amplification of DNA directly from bacterial lysate [25]. For Southern hybridization studies, a 1549-bp fragment of S. epidermidis 16s rRNA generated by P C R was labeled with digoxigenin 11-dUTP (Dig-11-dUTP) by the random priming procedure (Boehringer Mannheim).…”
Section: Methodsmentioning
confidence: 99%
“…Strain identification was performed by comparing the partial 16S rDNA sequence with those present in the Sequence Match of the Ribosomal Database Project II (RDP II), as described by Cole et al (2003) and (GTG) 5 genomic fingerprint analysis (Rademaker et al 2004). The DNA sequence of 16S rRNA genes (V1 to V3 variable regions) of the strains was determined after amplification as described elsewhere (Klijn et al 1991;Hoppe-Seyler et al 2003).…”
Section: Identification Of Strainsmentioning
confidence: 99%
“…4). Originally, both strains were classified in the subspecies lactis on phenotypic criteria but analysis of DNA-DNA reassociation [5], and 16S RNA sequences [104,105], direct gene sequence comparisons and Southern hybridization analysis with cloned chromosomal genes as probes [106] indicated that MG1363 and the closely related strains NCDO712, NCDO763 (ML3), NCDO505 (C2), LM2301 belong genotypically to the subspecies cremoris. The high degree of restriction polymorphism between IL1403 and MG1363 is consistent with the divergence of genomic sequences between L. lactis subsp, lactis…”
Section: Comparison Of the Genomic Mapsmentioning
confidence: 99%